Influence of surface passivation on indium arsenide nanowire band gap energies - Razavi, Pedram; Greer, James C. (Springer, 2019)
The interplay between surface chemistry and quantum confinement on the band gap energies of indium arsenide (InAs) nanowires is investigated by first principle computations as the surface-to-volume ratio increases with decreasing cross section. Electronic band structures are presented as determined by both density functional and hybrid density functional theory (DFT) calculations; the latter are used to provide improved band gap energy estimates over those from standard approximate DFT methods. Different monovalent chemical species with varying electron affinity are used to eliminate surface states to enable direct comparison between surface chemistry and quantum confinement. The influence of these effects on energy band gaps and electron effective masses is highlighted. It is found that many desirable properties in terms of electronic properties and the elimination of surface states for nanoscale field effect transistors fabricated using [100]-oriented InAs can be achieved. © 2019, The Minerals, Metals & Materials Society.